TWO NEW SPECIES OF PARABOEA (GESNERIACEAE) FROM PENINSULAR MALAYSIA AND THAILAND - Kiew, R. (Edinburgh Journal of Botany, 2010)
Paraboea gracillima Kiew (Gesneriaceae) is described from Perlis, Malaysia, and from Ban Khamphaengphen in Peninsular Thailand. Paraboea lambokensis Kiew is described from two hills in Kelantan, Malaysia. Both are restricted to limestone. Paraboea lambokensis is endemic in Peninsular Malaysia and is Critically Endangered, while P. gracillima, which is protected in the Perlis State Park, is categorised as Least Concern.